Ruang Lingkup Kebersamaan: Yasinan dan Gotong Royong Sebagai Pilar Ukhuwah Islamiyah - Fitriyani, Bebiyana (TAFANI: Jurnal Pengabdian Masyarakat, 2024)
In the context of Muslim society, the concept of ukhuwah Islamiyah or Islamic brotherhood has a very important role in building close relationships between fellow Muslims. Togetherness and cooperation are the key elements of this ukhuwah Islamiyah. The two forms of expression of this collaboration are Yasinan, which is often a deep religious moment, and Gotong Royong, which reflects a spirit of solidarity in everyday life. This article will explore the scope of togetherness in Islam with a focus on Yasinan and Gotong Royong, exploring how both of them become strong pillars in strengthening ukhuwah Islamiyah.